2022
DOI: 10.3390/ijms23073706
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule RAS Inhibitors as Anticancer Agents: Discovery, Development, and Mechanistic Studies

Abstract: Mutations of RAS oncogenes are responsible for about 30% of all human cancer types, including pancreatic, lung, and colorectal cancers. While KRAS1 is a pseudogene, mutation of KRAS2 (commonly known as KRAS oncogene) is directly or indirectly associated with human cancers. Among the RAS family, KRAS is the most abundant oncogene related to uncontrolled cellular proliferation to generate solid tumors in many types of cancer such as pancreatic carcinoma (over 80%), colon carcinoma (40–50%), lung carcinoma (30–50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 205 publications
(243 reference statements)
0
2
0
Order By: Relevance
“…These include molar refractivity, polar surface area, rotatable bonds, etc. Some commonly used small-molecule drugs are aspirin, atenolol, diazepam, diclofenac, ibuprofen, felodipine, omeprazole, phenytoin, and many others [ 22 , 23 , 24 , 25 ]. This review will shed light on the molecular characterization of TNBC, single drug targets, drug combinations, and different small molecules that are targeted to cause regulated or programmed cell death for the treatment of TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…These include molar refractivity, polar surface area, rotatable bonds, etc. Some commonly used small-molecule drugs are aspirin, atenolol, diazepam, diclofenac, ibuprofen, felodipine, omeprazole, phenytoin, and many others [ 22 , 23 , 24 , 25 ]. This review will shed light on the molecular characterization of TNBC, single drug targets, drug combinations, and different small molecules that are targeted to cause regulated or programmed cell death for the treatment of TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic compounds, as the most important organic compounds, are frequently present in molecules of interest in medicinal chemistry [1][2][3][4][5]. Heterocycles demonstrate pharmacological activity via several mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, DiFranco and coworkers [9] demonstrated that exposure to a neo-synthetic bis(indolyl)thiazole alkaloid analog, nortopsentin 234, leads to an initial reduction of proliferative and clonogenic potential of colorectal cancer cells. Hamdy et al [10] published the anti-apoptotic Bcl-2-inhibitory activity of synthesized 3-(6-substituted phenyl- [1,2,4]-triazolo [3,4-b]- [1,3,4]-thiadiazol-3-yl)-1H-indoles. Shao et al [11] synthesized and tested aminoindazole derivatives as new irreversible inhibitors of wild-type and gatekeeper mutant FGFR 4 .…”
Section: Introductionmentioning
confidence: 99%